Long-term change in habitat and vegetation in an ungrazed, estuarine salt marsh: Man-made foreland compared to young marsh development. (31st October 2019) - Hartmann, Karina; Stock, Martin
Abstract: Clay-rich salt marshes of mesotidal Wadden Sea coasts and of estuaries have been established mainly within artificial sedimentation fields in front of embankments. Natural salt marsh formation and natural range expansion outside artificial structures were rare. In the last three decades of this century natural marshes along the southern Wadden Sea coast of Schleswig-Holstein, Germany, started to grow outside groyne fields and extended on tidal mudflats. This growth happened without direct human influence and naturally structured marshes of considerable spatial dimension evolved. Due to a spread in recent decades, natural grown marshes in our study area – southern Schleswig-Holstein Wadden Sea coast - are younger than man-made marshes. Vegetation developed rapidly in response to fine-scaled geomorphological conditions. Meandering creeks and different surface elevation ranges of the developing natural salt marsh are special features. The naturally grown marshes show a high proportion of pioneer vegetation with Spartina anglica and Salicornia europaea . Succession proceeds fast and elevated parts of the marsh were rapidly colonised with marsh vegetation of Puccinellia maritima and Aster tripolium in the lower marsh to late successional stages, like Halimione portulacoides and Elymus athericus, on the higher elevated parts. Strikingly, median elevations of the vegetation zones in the natural marsh were several centimetres lower than those of the man-made marsh. The largest difference between both marsh types was the characteristic and the extent of drainage systems. Naturally grown marshes have a natural developed, fine-branched and four times shorter drainage system than man-made marshes with a dense drainage structure.